Dead is a killer tune - Perez, Marlene (Perez, Marlene. Dead is., 2012)
"Jessica and the other viragos must find who is responsible for the haunting music that is compelling Nightshade residents to commit crimes. Can they find out who is "behind the music" before it's too late?"--